Melodies Unheard : Essays on the Mysteries of Poetry - Hecht, Anthony, 1923-2004 (Book collections on Project MUSE., 2019)
The fruit of a lifetime's reading and thinking about literature, its delights and its responsibilities, this book by acclaimed poet and critic Anthony Hecht explores the mysteries of poetry, offering profound insight into poetic form, meter, rhyme, and meaning. Ranging from Renaissance to contemporary poets, Hecht considers the work of Shakespeare, Sidney, and Noel Housman, Hopkins, Eliot, and Auden Frost, Bishop, and Wilbur Amichai, Simic, and Heaney. Stepping back from individual poets, Hecht muses on rhyme and on meter, and also discusses St. Paul's Epistle to the Galatians and Melville's Moby-Dick. Uniting these diverse subjects is Hecht's preoccupation with the careful deployment of words, the richness and versatility of language and of those who use it well.